Pengaruh Jenis Pendingin Dan Variasi Sudut Potong Terhadap Kekasaran Permukaan Bubut Baja SCM 440 - Angga, Muhammad Angga Pratama; Kurniawan, Zaldy; Yudo, Eko (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Abstract At present it is not surprising that industrial competition continues in different parts of production according to the form of business. This is entirely due to the development of science and technology which is increasingly advanced day by day. As well as in the field of machining, namely machine tools and production, production machines that play an important role in the course of industrial activities, one of which is the lathe. The material used in this test is alloy steel SCM 440, this material is medium carbon chromium molybdenum alloy steel, SCM 440 alloy steel contains chromium and molybdnum. Has an alloy composition of 0.38-0.43% C, 0.90-1.20% Cr, 0.15-035% Si, 0.60-0.85% Mn, 0.15-0.30% Mo, and 0.03 max p/s. The diameter of the BK tube is Ø25 x 100 mm. This study uses the Taguchi method. The parameters used are the angle of cut, type of coolant and feeding speed. The optimum parameters for obtaining a low roughness value are the cutting angle of 13°, the type of cooling cutting oil and the feeding speed of 0.040 mm. With a S/N ratio of -10.396.